PENERAPAN PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR SISWA SMA - Amanda; Yudi Darma; Nurmaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the effect of differentiated learning implementation on mathematical communication skills of high school students, especially in terms of their level of learning independence. The research method used was quasi-experiment with pre-test-post-test design. The research sample was high school students. The results showed that there was a significant improvement in the mathematical communication skills of students in the experimental group. In addition, a positive correlation was found between students' learning independence and the improvement of their mathematical communication skills. The implication of this study is that differentiated learning can be an effective alternative to improve students' mathematical communication skills, especially for students with a high level of learning independence.